Linguistic representations and memory architectures: The devil is in the details. (2016) - Chacón, Dustin Alfonso; Momma, Shota; Phillips, Colin
Abstract: Attempts to explain linguistic phenomena as consequences of memory constraints require detailed specification of linguistic representations and memory architectures alike. We discuss examples of supposed locality biases in language comprehension and production, and their link to memory constraints. Findings do not generally favor Christiansen & Chater's (C&C's) approach. We discuss connections to debates that stretch back to the nineteenth century.